The Etymology and History of the Placename "Des Moines". (June 2015) - McCafferty, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> The original form of the placename "Des Moines" was created by a seventeenth-century French mapmaker. It was given a new life — and its present form — by an early nineteenth-century French-speaking mapmaker. However, the name "Moines" comes from an American Indian tribe name that has undergone extensive and interesting changes since it was first recorded around the summer solstice in the year 1673 by the Jesuit missionary-explorer Jacques Marquette. The following article presents this placename's history and explains its unusual meaning in the Miami-Illinois language.